Improvement of microbial transglutaminase‐induced gelation of β‐conglycinin by conjugation with dextran. (11th November 2013) - Zhang, Jinbo; Wu, Nana; Yang, Xiaoquan; He, Xiuting; Guo, Jian; Zhu, Jianhua
Summary This work focused on the effect of glycosylation on the gelation ability of β‐conglycinin induced by microbial transglutaminase (MTGase). Rheological results indicated that the gels of β‐conglycinin‐dextran conjugate products exhibited higher G′ value (172.2 ± 8.6 Pa) compared with those of dry‐heated β‐conglycinin (75.2 ± 5.1 Pa), β‐conglycinin (53.3 ± 4.0 Pa) and β‐conglycinin‐dextran mixture (38.6 ± 2.6 Pa) after 4 h incubation with MTGase. The gels prepared from β‐conglycinin‐dextran conjugate products had higher hardness, fracturability, springiness and cohesiveness values determined by textural profile analysis. The turbidity of β‐conglycinin‐dextran conjugate products solution incubated with MTGase increased faster than those of the other three protein samples. The conjugated dextran in β‐conglycinin‐dextran conjugate products could inhibit extensive protein–protein interactions which might result in the formation of more ordered and stronger gel network structures during MTGase cross‐linking process. A compact and homogeneous gel networks in β‐conglycinin‐dextran conjugate products gels were also observed by scanning electron microscopy.